Infectious scleritis: a review of etiologies, clinical features, and management strategies - Sharma, Supriya; Sheth, Jay U.; Murthy, Somasheila I. (Frontiers in Ophthalmology, 2025)
Infectious scleritis is a severe and potentially vision-threatening inflammation of the sclera caused by microbial invasion. Unlike autoimmune scleritis, infectious scleritis is less common with a prevalence of 5%–10% of all cases of scleritis. The initial clinical presentation may often resemble autoimmune scleritis, thus resulting in a delayed diagnosis and poorer outcomes. A high level of suspicion is required in such cases and risk factors such as with a history of trauma or surgery and worsening or refractory to immunosuppressive medications as these may well be infectious. While in established cases, the classical clinical features enable us to diagnose as infectious etiology without much difficulty, the management remains a challenge. Majority of these cases require an aggressive approach with a combination of antimicrobial therapy and surgical treatment. Poor prognostic factors include delayed diagnosis, fungal etiology, and the presence of keratitis or endophthalmitis. In this review, the authors have summarized the prevalence, clinical and microbiological profile, and management strategies of infectious scleritis and their outcomes.